A incidência do mito em "Confissões de uma viúva moça" e "A mulher de preto" (contos fluminenses), de Machado de Assis - Zafalon, Míriam (2010)
This paper discusses the presence of classic Greek and Biblical myth in the tales "The Woman in Black" and "Confessions of a widow lady", from the work Fluminenses Tales(1870), of Machado de Assis. The choice reflects the concern of working tales of an anthology little explored by scholars of Machado's (Machadian) work. The meaning of myth has been discussed from the concepts of scholars such as Jean-Pierre Vernant, Junito de Souza Brandão, Joseph Campbell, Ernest Cassirer, Mircea Eliade, E.M Mielientiski, among others. Understanding myth as a narrative set consecrated by tradition and that showed, at least in the origin, the irruption of the sacred or the supernatural in the world, but, in posterior period assumed an abstract meaning, we intend to analyze how Machado de Assis used the traditional myths in the composition of some of his characters and plots, modernizing them, adapting them to his time, without, however, diminish the aura of his immortality. In the selected tales, it was attempted to verify the situations of the characters that suggest mythological aspects, namely: Odysseus, Penelope and Telemachus, characters of the Homeric work Odyssey, recalled in the tale "The woman in Black", Eve, Bible character, Oedipus, the Sphinx and the Hydra of lerna, Greek pagan myths, updated in the narrative of "Confessions of a widow lady." The analysis was carried out having as a theoretical referential the Aesthetics of reception, theory created by Jauss (1994) and Iser (1999), which privileges the presence of the reader in the engagement with written text and the author's point of view. As a result, a reading of the tales identified for the analysis is presented, conferring the traditional and the modern, allowing the confirmation of the unceasing update of the classical and biblical mythology, under the genial sloping of Machado. It is thus a distinguished contribution to the studies of the tales of Machado de Assis, an eternal source of prospects and new studies.